The statistics and calculus workshop : a comprehensive introduction to mathematics in Python for artificial intelligence applications /: a comprehensive introduction to mathematics in Python for artificial intelligence applications. (2020) - Farrell, Peter, 1966-; Fuentes, Alvaro; Kolhe, Ajinkya Sudhir; Nguyễn, Quân; Sarver, Alexander Joseph; Tsatsos, Marios
No abstract available